2018
DOI: 10.3389/fpls.2018.00179
|View full text |Cite
|
Sign up to set email alerts
|

SKL1 Is Essential for Chloroplast Development in Arabidopsis

Abstract: The Arabidopsis shikimate kinase-like 1 (skl1-8) mutant is characterized by a pigment-defective phenotype. Although the related phenotypical defect mainly has been attributed to the blocking of chloroplast development, the molecular functions of SKL1 remain largely unknown. In this study, we combined multiple approaches to investigate the potential functions of SKL1. Results showed that the skl1-8 mutant exhibited an albino phenotype and had dramatically reduced chlorophyll content as a consequence of a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…Similarly, mutation of SVR9 , a chloroplast‐localized translation initiation factor, causes abnormal physiological development and DR5:GUS staining revealed enhanced auxin activity and altered auxin distribution in the leaves of svr9 mutants (Zheng et al ., 2016). Furthermore, Arabidopsis skl1‐8 mutants exhibit albinism, resulting from dramatically reduced chlorophyll levels and downregulation of genes involved in photosynthesis (including chloroplast genes) and auxin transport and response, suggesting SKL1 is involved in auxin‐related pathways during chloroplast development (Xu et al ., 2018). Moreover, evidence for the link between auxin and chloroplast development extends beyond Arabidopsis to tomato and rice, but there is inconsistency in the reported relationship (Melo et al ., 2016; Chen et al ., 2019; Yuan et al ., 2019).…”
Section: How Does Auxin Influence Chloroplast Development and Physiol...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, mutation of SVR9 , a chloroplast‐localized translation initiation factor, causes abnormal physiological development and DR5:GUS staining revealed enhanced auxin activity and altered auxin distribution in the leaves of svr9 mutants (Zheng et al ., 2016). Furthermore, Arabidopsis skl1‐8 mutants exhibit albinism, resulting from dramatically reduced chlorophyll levels and downregulation of genes involved in photosynthesis (including chloroplast genes) and auxin transport and response, suggesting SKL1 is involved in auxin‐related pathways during chloroplast development (Xu et al ., 2018). Moreover, evidence for the link between auxin and chloroplast development extends beyond Arabidopsis to tomato and rice, but there is inconsistency in the reported relationship (Melo et al ., 2016; Chen et al ., 2019; Yuan et al ., 2019).…”
Section: How Does Auxin Influence Chloroplast Development and Physiol...mentioning
confidence: 99%
“…It is clear that IAA level correlates with photosynthetic activity and chlorophyll levels (Batista‐Silva et al ., 2019; L. Wang et al ., 2019; Li et al ., 2019; Yuan et al ., 2019; Mir et al ., 2020). There have also been numerous studies that show that expression of genes involved in photosynthesis (including chloroplast genes) are associated with auxin homeostasis, transport or signalling (Chen et al ., 2015, 2019; Xu et al ., 2018; Yuan et al ., 2019) and auxin‐induced transcriptional activity affects mitochondrial function (Kerchev et al ., 2014). However, we hypothesize that there is a further level of regulation of organelle development at the translation level (Fig.…”
Section: Are There Testable Hypotheses To Establish Mechanisms That L...mentioning
confidence: 99%
“…Premature leaf senescence is often coupled with defective photosynthesis in plants [ 27 ]. To test this possibility, we examined the photosynthetic parameters of flag leaves in WT and psl85 at the heading stage.…”
Section: Resultsmentioning
confidence: 99%
“…These ndings indicate that these novel SK-like homologs acquired novel functions during a long period of evolution. In Arabidopsis, for example, SKL1 affects chloroplast biogenesis by regulating auxin pathways (Xu et al 2018), while AtSK1 and AtSK2 were found to show differential expression under biotic and abiotic stress conditions (Fucile et al 2008). However, direct experimental evidence of the role of AtSK1 and AtSK2 in abiotic stress remains largely lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The Arabidopsis genome contains two genes (AtSK1 and AtSK2) encoding functional SK enzymes, and two SK homologs, shikimate kinase-like 1 (AtSKL1) and 2 (AtSKL2), which have evolved from SK gene duplicates and do not possess SK enzyme activity in vitro (Fucile et al 2008). Research has shown that AtSKL1 is crucial for chloroplast development, while AtSKL2 has acquired a protein-protein interaction domain that is important for adaptive molecular evolution (Fucile et al 2008;Xu et al 2018). Meanwhile, three SK genes (OsSK1, OsSK2 and OsSK3) and two SK homologs (OsSKL1 and OsSKL2) have so far been identi ed in rice, and while these rice SK genes are thought to contribute to defense responses and panicle development (Kasai et al 2005;Tohge et al 2013), little is known about the function of OsSKL1 and OsSKL2.…”
mentioning
confidence: 99%